2021
DOI: 10.15517/rbt.v69i2.45046
|View full text |Cite
|
Sign up to set email alerts
|

Las cabras como dispersores de semillas: aportes y limitaciones para la regeneración del bosque tropical estacionalmente seco de Ecuador

Abstract: Introducción: Los bosques tropicales estacionalmente secos están sujetos a procesos de degradación crónica que ponen en riesgo su diversidad. La ganadería intensiva dentro de los remanentes de bosque se plantea como una de las principales causas de estos procesos de degradación. Sin embargo, el ganado también podría estar cumpliendo el rol de dispersor de semillas para algunas especies. Objetivo: Evaluar el rol de las cabras en la dispersión de semillas de especies leñosas y las posibles consecuencias de su co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In SDTFs, the ease of access to humans into the forest is a good surrogate of chronic disturbance (Cueva Ortiz et al, 2019). In this region, goats are released every day to forage freely into the forest, and with the sunset, they return to the stables located near the owner's houses (Espinosa et al, 2021). Therefore, the distance of the populated centers to the forest is directly related to the logging and livestock loading history that the forest has supported (Cueva Ortiz et al, 2019).…”
Section: Forest Characterization At the Cell Scalementioning
confidence: 99%
See 1 more Smart Citation
“…In SDTFs, the ease of access to humans into the forest is a good surrogate of chronic disturbance (Cueva Ortiz et al, 2019). In this region, goats are released every day to forage freely into the forest, and with the sunset, they return to the stables located near the owner's houses (Espinosa et al, 2021). Therefore, the distance of the populated centers to the forest is directly related to the logging and livestock loading history that the forest has supported (Cueva Ortiz et al, 2019).…”
Section: Forest Characterization At the Cell Scalementioning
confidence: 99%
“…Therefore, we did not consider pathways from tree density to productivity and structural complexity, nor a pathway from chronic disturbance to productivity. Based on this model we hypothesized that indirect pathways could explain the loss of species richness better than direct ones because (i) the loss of species through selective elimination can be compensated with the establishment of generalist or invasive species, such as those dispersed by livestock (Espinosa et al, 2021). (ii) There is evidence that in this stressful ecosystem the environmental filtering and positive plant-plant interactions determine the community structure and plant diversity (Espinosa et al, 2016;Gusmán-M et al, 2018), thus the exacerbation of habitat filtering exerted by changes in the micro-environmental conditions could have strong consequences on the plant species richness.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, chronic disturbance is favoring species with greater tolerance to stress, most of them bearing pods an autochorous dispersal strategy. This result is not a surprise since autochorous species have showed to be opportunistic pioneers and, consequently, more common in disturbed habitats (Hilje et al 2015), but also some of those species are secondary dispersed by goats (Espinosa et al 2021). In our study area, most of autochorous species are legumes with seeds cover by hard coats (Jara-Guerrero et al…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, Silva et al (2020) reported that the taxonomic richness of species with eshy fruits, and those with zoochoric dispersal were affected negatively by an increase in aridity but positively by the wood extraction or livestock grazing in SDTF of the Caatinga region. Recent research at SDTF in southwestern Ecuador showed that free-foraging goats in the forest disperse mainly legume seeds, particularly those of species with dry pods (Espinosa et al 2021); therefore, in chronically disturbed areas, where wild dispersers are almost excluded, those species with specialized traits for genuine animal-dispersal, eshy fruits, may be adversely affected. On the other hand, Maza-Villalobos et al (2022) reported for SDTF of Mexico that the presence of cattle negatively affected the size and weight of fruits, and the seed number per fruit, while the weight and size of seeds were positively affected.…”
Section: Introductionmentioning
confidence: 99%
“…The farms were selected by the RAND function in Excel ® (v. 17.0, Microsoft, Redmond, WA, USA) using the database provided by the Agricultural Public Information System (SIPA, by the acronym in Spanish) of the Ministry of Agriculture and Livestock of Ecuador [ 19 ]. Local breeders used to release the goats every day to forage freely in the forest, and at sunset, the animals returned to the dirt-floored stables located near the owner’s houses [ 20 ].…”
Section: Methodsmentioning
confidence: 99%